Characterisation on the role of non B lymphocytes during infectious bursal disease virus infection. - Omar, Abdul Rahman; Rasoli, Mehdi; Moeini, Hassan; Swee, Keong Yeap; Kaiser, Pete; Bejo, Mohd Hair; Ideris, Aini; Sheau, Wei Tan
Infectious bursal disease (IBD) is caused by IBD virus (IBDV), a highly infectious Iymphotropic virus that induces cytocidal effect on chicken B lymphocytes of bursa of Fabricius. Hence, the disease been considered to have the most impact due to its immunosuppressive effects in young birds. However, the effects of the virus on non B lymphocytes are poorly characterised. In our study, we have analysed the interaction of IBDV with various primary and secondary cell cultures namely, transformed chicken macrophage-like celiline(HD11), transformed chicken T cell line (CcmPI-C1-vick)j primary bone marrow dendritic cell and primary IEL natural killer cells. In vitro cytocidal effect of IBDV toward HD 11 cell line showed evidence of apoptosis where 6% of cell undergo early at 24 hours follow by 11% of cell undergo late apoptosis that associated with pro-inflammation cytokines up-regulation. This result was similar with our in vivo finding where infiltration of macrophage associated with high expression of IL-1 alpha, IFN-y and IL-12a were observed in both and bursa of Fabricius post IBDV infection. IBDV was also found to be present in primary dendritic cell after in vivo infection. Dendritic cell may also partially contribute to up-regulation of the above in vivo pro-inflammatory cytokines post IBDV infection. However, ConA-Cl-vick maintained high viability as untreated control after 48 hours post-infection with IBDV in vitro. Although, CONA-Cl-vick T cell line was not responding again IBDV infection in vitro, CD4 T cells infiltration in bursa of Fabricius was observed post IBDV infection. This phenomenon was similar with 28.4+ IEL NK cells which interact poorly with IBDV in vitro, but the population of 28.4+ IEL NK cell was increased post IBDV infection. The roles of these cells in modulating IBDV infections are currently being studied.